THE RESULTS OF THE SEARCH FOR LABORATORY SIGNS OF AUTOIMMUNE REACTIONS TO CEREBRAL AND EXTRACEREBRAL AUTOANTIGENS IN CHILDREN WITH AUTISM SPECTRUM DISORDERS ASSOCIATED WITH GENETIC DEFICIENCY OF THE FOLATE CYCLE - D.V. Maltsev (Медична наука України, 2021)
Relevance. The results of five meta-analyzes of randomized controlled clinical trials indicate an association between genetic deficiency of the folate cycle (GDFC) and autism spectrum disorders (ASD) in children. Autoimmune mechanisms play a special role in the pathogenesis of encephalopathy in children with ASD associated with GDFC.